Fabrication and characterization of epoxy resin–barium titanate at G-band using waveguide technique - Nurulfadzilah, Hasan; Nur Shahira, Mat Hussain; Nur Hazimah Syazana, Abdul Razak; Ahmad Syahiman, Mohd Shah; Mohamad Shaiful, Abdul Karim (IOP Publishing, 2021)
In this paper, fabrication process of epoxy resin-barium titanate nanocomposite and measurement of its complex permittivity are presented. The material is prepared by mechanical mixing of epoxy resin and barium titanate nanopowder. The nanocomposite is intended to be used as high permittivity microstrip antenna substrate, which requires accurate measurement of its electrical characteristics. Thus, characterization of materials is done using waveguide technique, which does not require a precise machining of sample's width and thickness, and does not utilize small reflection coefficient, which can cause error in measurement. The complex permittivity of the nanocomposite is measured in G-band (4 to 6 GHz). Then, the measured values are compared with prediction method, Lichtnecker and Maxwell-Garnet method. The results show that the measured permittivity of composite materials are in good range with prediction method, while the measurements of loss tangent show that the developed materials are low-loss and suitable to be used as substrate of antenna.